THE EFFECT OF PERSONAL DEVELOPMENT ON EMPLOYEES OF PUBLIC HOUSING EMPLOYEES AND HOUSING SERVICES IN MEDAN CITY - Wan Dian Safina; Henny Andriyani Wirananda (UPMI Management, 2022)
This study is titled the Impact of personal development on employees of public housing and housing services in Medan City. This study aimed to determine whether human resource development affects employee performance in the Public Housing and Settlement Office of Medan City. The data used in this study is primary data using a research instrument in the form of a questionnaire. The research population was 160 employees of the Medan City Housing and Settlements Office. In the end, a random sample of 48 respondents was used. The method used in this research is a quantitative descriptive method. The T-test result was 7,871, so staff development positively and significantly impacts the performance of housing and services workers in Medan City. It is recommended to encourage improving the performance of public housing and housing services workers in Medan City; managers who care about efforts to develop human resources, primarily through training, are needed. Keywords:Human Resource Development, Personal Development, Employee Performance JEL Classification: L20, L25, M10